Porojen talviruokinta ja sen vaikutukset porojen käyttäytymiseen, poronhoitokäytäntöihin ja ympäristöön - Anna Skarin; Minna Turunen; Svein Morten Eilertsen; Heidi Rautiainen; Tim Horstkotte; Ole Nils Aslak Baal; Leif-Anders Blind; Ove Emanuelsson; Ove Hallergren; Anna-Marja Kaddik; Lars-Tomas Labba; Helén Larsson; et al. (Rangifer, 2024)
This report is based on the results from a Nordic network project funded by The Nordic Joint Committee for Agricultural and Food Research (NKJ) during the years 2021-2022. This network was created to encourage further cross-border discussions about the prospects of winter feeding of reindeer. In reindeer husbandry winter feeding has increased during the last decades due to competing land use activities and climate change. Herders in Norway, Sweden and Finland have previously raised concerns about the benefits and risks associated to the increasing need of winter feeding of reindeer in all three countries. The report, published in Swedish, Norwegian, Finnish and North Sámi, and covers the main findings from a series of preparatory workshops within each country and a main workshop in Arvidsjaur 8-9 June 2022. During the network activities, reindeer herders, researchers and managers discussed the effects of feeding on reindeer behaviour, herding practices and the environment. The two main topics discussed at the preparatory workshops were 1) the short- and long-term effects of winter feeding on reindeer behaviour, and 2) local to large scale effects of feeding on the environment and the natural pastures. During the main workshop, discussions were held about reasons for feeding of reindeer, the preconditions of feeding in the three countries, how winter feeding is usually performed, and best practices in relation to reindeer behaviour and the environment. The work aimed at promoting knowledge exchange on winter feeding of reindeer among all participants to help find solutions and mitigation actions to avoid changes in reindeer behaviour and negative effects of feeding on reindeer, reindeer herding and the environment. The report is aimed at herders, managers, as well as other land users, authorities and policymakers to give information on what was discussed and a summary of the challenges related to winter feeding and effects on reindeer behaviour and reindeer husbandry, and the environment. Rangifer Report No 19 is ...